Financing and Managing Projects, Volume I : a Guide for Executives and Professionals. - Dhameja, Nand L. (Business Expert Press, 2015)
Project is an instrument of change and no project is complete unless its objective is achieved. Every project is specific and unique. The term project is expanding and ever changing; executives, regulatory bodies and other stakeholders have to look into the managerial and financing aspects of a project. This Volume deals with the managerial aspects of a project, i.e., project phases, its formulation and appraisal techniques; there is no one best technique and executive judgment is essential. Every chapter begins with the objectives to be delivered and at the end includes some project instances, brief case examples and case studies so as to provide an analytical kit for executives and professionals The book makes for a lucid reading and works as a guide for the reader. It has been written based on our experience(s) gained and also the feedback collected from teaching, training and delivering various consultancy projects. Suggestions/comments and feedback are welcome.